Annual Plant Reviews Online 2018
DOI: 10.1002/9781119312994.apr0495
|View full text |Cite
|
Sign up to set email alerts
|

Development in the Wild: Phenotypic Plasticity

Abstract: Development of organisms in the wild occurs in ecologically variable environments. Phenotypic plasticity occurs when a single genotype alters its phenotype in response to its environment. Some traits are more plastic than others, and whether a particular trait evolves plasticity depends on the degree of environmental variation experienced by that trait, the quality of environment‐dependent natural selection on that trait, and the strength of genetic correlations between the trait expressed in different environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 122 publications
0
1
0
Order By: Relevance
“…The most successful individuals will be those with plastic life-history strategies that allow optimal resource acquisition and allocation (Barrett, Eckert, & Husband, 1993). However, much attention has been paid to single-taxon responses, whereas comparative works of phylogenetically close taxa showed that the phenotypic plasticity can vary substantially in the pattern and amount of variation exhibited (Barrett & Wilson, 1981;Donohue, 2018;Schlichting & Levin, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The most successful individuals will be those with plastic life-history strategies that allow optimal resource acquisition and allocation (Barrett, Eckert, & Husband, 1993). However, much attention has been paid to single-taxon responses, whereas comparative works of phylogenetically close taxa showed that the phenotypic plasticity can vary substantially in the pattern and amount of variation exhibited (Barrett & Wilson, 1981;Donohue, 2018;Schlichting & Levin, 1984).…”
Section: Introductionmentioning
confidence: 99%